Electrical components part I [ resistors, batteries, and switches - Duffy, James E. (Electricity and eletronics, 2006)
"Fixed resistors, variable resistors, ballast resistors, batteries, and various types of switches are explained in this program. Computer animation, component cut-aways, and lab experiements are used to demonstrate how these basic components function." - cover sleeve